Electroconvulsive therapy modulates the interplay between depressive symptoms in difficult-to-treat depression: A longitudinal network analysis - Marialaura Lussignoli; Marco Bortolomasi; Giulia Perusi; Giorgio Pigato; Alessandra Minelli; Fabio Sambataro (European Psychiatry, 2025)
Abstract